Antineuronal Antibodies and Infectious Pathogens in Severe Acute Pediatric Encephalitis. (January 2014) - Lin, Jainn-Jim; Lin, Kuang-Lin; Chiu, Cheng-Hsun; Hsia, Shao-Hsuan; Wang, Huei-Shyong; Chou, I-Jun; Lin, Yun-Tong; ,
The pathogenesis of acute encephalitis is divided into either direct infection or by immune-mediated inflammation, but the cause is still unknown. This retrospective study aimed to screen antineuronal antibodies in children with severe acute encephalitis. Thirty-four children (22 boys and 12 girls) underwent assessments such as antineuronal antibodies survey for autoimmune encephalitis and polymerase chain reaction/viral culture and antibody assays for all commonly recognized causes of infectious encephalitis. Sixteen (47.1%) were positive for autoantibodies, including antiglutamic acid decarboxylase antibodies in 16 and voltage-gated potassium channel complex antibodies in 1. Sixteen patients (47.1%) had presumed infectious etiologies, including 6 with influenza, 6 with Mycoplasma pneumoniae, 3 with enterovirus, and 1 with herpes simplex virus. In this study, influenza and Mycoplasma pneumoniae infection are the main presumed causes of severe acute encephalitis in children, although an immune-mediated mechanism may also play a role.